The Effect of Banana Skin on Acne Vulgaris - Amirul Amalia; Sulistiyowati Sulistiyowati (Jurnal Keperawatan, 2019)
ABSTRACTAcne vulgaris is a common inflammatory condition in the pilosebaceous unit that occurs in female adolescents and young adults characterized by blackheads, papules, pustules, nodules. A non-medical treatment is one of intervention which can be done to treat Acne vulgaris. One example of non-medical treatment is herbal therapy using banana skin. Banana skin contains antioxidants, anti-fungus, therefore it can accelerate the healing process, help to lift dead skin cells, and prevent the risk of new acne. This study aimed to determine the effectiveness of banana skin to treat Acne Vulgaris. This research used a pre-experimental with one group pretest and posttest design. The respondents were female adolescents in Gedangan Village Sukodadi Lamongan who include in the inclusion criteria. The data were analyzed using Wilcoxon Tests. The results showed that banana skin was found to be effectively decreased the symptoms of Acne vulgaris (p-value < 0.05). In conclusion, this study are expected to be additional information of the effect of a banana skin on Acne vulgaris in adolescents, and it may provide input for clinicians to manage Acne Vulgaris, especially in female adolescents.Keyword: Acne Vulgaris, Banana Skin, Female Adolescents